LINKING PLATELET LARGER CELL RATIO (P-LCR) AND URIC ACID LEVEL WITH VARIOUS COMPONENTS OF METABOLIC SYNDROME - DHARMIK S. PATEL; BHAKTI N. GAMI; KILLOL N. DESAI (International Journal of Pharma and Bio Sciences, 2015)
Serum uric acid and Platelet larger cell ratio play a significant role in cardiac and metabolic disorders in developing countries like India. The metabolic syndrome is associated with diabetes and other cardiovascular diseases, but the link between such blood parameters and metabolic syndrome have not been demonstrated decisively.Total 87 consecutive patients (44 metabolic syndrome positive and 43 metabolic syndrome negative) were recruited. Uric acid, P-LCR and other variables were measured using latest available methods. Metabolic syndrome was diagnosed using criteria given as joint statement by many international groups in 2009.Uric acid level and P-LCR both are significantly higher in individuals with metabolic syndrome.Serum uric acid and P-LCR level may be used as an additional component of metabolic syndrome.